2013
DOI: 10.1111/jac.12045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Stress on the Photosynthetic Characteristics in Flag Leaves at the Grain‐Filling Stage of Different Heat‐Resistant Winter Wheat Varieties

Abstract: Heat stress has become an increasingly important factor in limiting wheat yields. In northern China, high temperature (>30°C) during the grain filling is one of the major constraints in increasing wheat productivity. We used two winter wheat (Triticum aestivum L.) cultivars with different sensitivities to heat stress (Jimai 22 'JM22', low sensitivity and Xinmai 26 'XM26', high sensitivity) to study the various aspects of photosynthetic characteristics during the grain filling stage under heat stress. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
102
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(116 citation statements)
references
References 45 publications
11
102
1
2
Order By: Relevance
“…This different physiological behaviour suggests that the effects of heat stress were genotype dependent, as also highlighted by Feng et al. ().…”
Section: Discussionmentioning
confidence: 58%
“…This different physiological behaviour suggests that the effects of heat stress were genotype dependent, as also highlighted by Feng et al. ().…”
Section: Discussionmentioning
confidence: 58%
“…Previous research also indicated that the impact of heat and drought on crop growth and yield varied between wheat cultivars. Wheat cultivars which are tolerant to high temperatures have been specified by the maintenance of photosynthesis, chlorophyll content and an extended grain filling duration even at high temperatures (Al‐Khatib & Paulsen, ; Feng et al., ; Tahir & Nakata, ; Wardlaw, Dawson, Munibi, & Fewster, ). However, little is known about the response of different cultivars to heat and drought interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Among the myriad of physiological processes in plants, photosynthesis is one of the heat‐sensitive to inhibition, with inhibition occurring at temperatures only slightly above those required for optimal growth (Salvucci , Feng et al. ). This inhibition has been linked to various factors, including the stomatal conductance and electron transfer, and thermal instability of Rubisco's molecular chaperone and Rubisco activase (Feller et al.…”
Section: Introductionmentioning
confidence: 99%